TP7.2.1 Outcomes of Modified Karydakis flap in the surgical management of sacrococcygeal pilonidal disease: A single surgeon's experience. (28th October 2021) - Alam, Fahreyar; Farooq, Dilawar; Theofilis, Aris; Wooler, Harry; Payne, Richard
Abstract: Aim: To determine the incidence of post-operative complications of patients with sacrococcygeal pilonidal disease who were treated with the Modified Karydakis flap with a specific management bundle. Primary outcomes assessed included the post-operative incidence of seroma, haematoma, SSI, deep SSI, wound dehiscence, re-admissions, return to theatre and flap necrosis. Secondary outcome evaluated was recurrence at 6 month follow up. Method: It was a retrospective analysis of a single surgeon's (FA's) practice results of Modified Karydakis flaps on patients with sacrococcygeal pilonidal disease who were managed according to a specific protocol. Data was collected between June 2017 and June 2020. 96 patients were analysed, of which 9 were excluded as they had excision without closure. Pre, per and post-operative management for the remaining 87 patients was according to a standardised protocol. Data was collected from patient's notes and from prospectively and retrospectively maintained patient data bases (Theatre System, Medway). Results: Primary outcomes: Seroma: 8/87 (9.2%) Haematoma: 1/87 (1.2%) SSI: 10/87 (11.5%) Deep SSI: 4/87 (4.6%) Superficial dehiscence: 7/87 (8.0%) Re-admission: 4/87 (4.6%) Return to theatre: 0 (0%) Flap necrosis: 0 (0%) Secondary outcome: Recurrence at 6 months: 2/87 (2.3%) Conclusions: Good surgical results can be obtained with Modified Karadakis flap, provided meticulous surgical technique is applied. Placement of a suction drain for a minimum of 72 hours reduces incidence of post-operative haematoma and seroma formation. Three post-operative doses of broad spectrum intravenous antibiotics followed by 5 days of oral antibiotics helps reduce post-operative infections.